Kewenangan Notaris Dalam Memberikan Penyuluhan Hukum Terkait Dengan Pembuatan Akta - Dindianingrat, Nyoman Yashinta; Yogantara S, Pande; Sumardika, I Nyoman (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 9 No 03 (2024), 2024)
The purpose of this writing is to determine the nature and limits of a Notary's authority to provide legal counseling in making deeds. This journal uses a normative legal research method to examine the issues surrounding the regulation of notaries' responsibilities in providing legal advice to their clients. Legal counseling by notaries is very important to provide legal knowledge to the community regarding authentic deeds, which helps to create a society that understands the law and is able to utilize it according to their needs. Notaries only provide guidance to clients who will create deeds with them. The legal counseling given by notaries is a form of explanation regarding the process of creating authentic deeds to individuals or parties who come to their office. In drafting an authentic deed, a notary must adhere to the applicable norms and rules to ensure that the resulting deed does not create legal issues or conflicts.